Sejarah dan Praktek Manajemen ZISWAF di Indonesia - Febriani, Eli; Yantika, Kiky Razroma; Hidayati, Nurvina; Alfin, Aidil (Jurnal Ilmiah Global Education, 2024)
This study examines the history and management practices of ZISWAF (Zakat, Infaq, Sadaqah, and Waqf) in Indonesia through literature studies using secondary data from various library sources, reports of zakat institutions, and interviews with zakat managers and beneficiaries. The results of the study show that the management of ZISWAF in Indonesia has undergone a significant evolution from the Dutch colonial period to the modern era. These developments include five important periods: the Dutch colonial period with the issuance of Ordinance No. 6200, the Old Order period which was marked by efforts to integrate zakat in the state system, the New Order period with the establishment of BAZIS, the era of Law No. 38 of 1999 which provided a formal legal basis for zakat management, to the era of Law No. 23 of 2011 which strengthened the zakat management system with Islamic sharia principles. trust, utility, justice, legal certainty, integrated, and accountability.